Vasopressin and Breathing: Review of Evidence for Respiratory Effects of the Antidiuretic Hormone - Proczka, Michał; Przybylski, Jacek; Cudnoch-Jędrzejewska, Agnieszka; Szczepańska-Sadowska, Ewa; Żera, Tymoteusz (Frontiers in Physiology, 2021)
Vasopressin (AVP) is a key neurohormone involved in the regulation of body functions. Due to its urine-concentrating effect in the kidneys, it is often referred to as antidiuretic hormone. Besides its antidiuretic renal effects, AVP is a potent neurohormone involved in the regulation of arterial blood pressure, sympathetic activity, baroreflex sensitivity, glucose homeostasis, release of glucocorticoids and catecholamines, stress response, anxiety, memory, and behaviour. Vasopressin is synthetised in the paraventricular and supraoptic nuclei of the hypothalamus and released into the circulation from the posterior lobe of the pituitary gland together with a C-terminal fragment of pro-vasopressin, known as copeptin. Additionally, vasopressinergic neurons project from the hypothalamus to the brainstem nuclei. Increased release of AVP into the circulation and elevated levels of its surrogate marker copeptin are found in pulmonary diseases, arterial hypertension, heart failure, obstructive sleep apnoea, severe infections, COVID-19 due to SARS-CoV-2 infection, and brain injuries. All these conditions are usually accompanied by respiratory disturbances. The main stimuli that trigger AVP release include hyperosmolality, hypovolaemia, hypotension, hypoxia, hypoglycaemia, strenuous exercise, and angiotensin II and the same stimuli are known to affect pulmonary ventilation. In this light, we hypothesise that increased AVP release and changes in ventilation are not coincidental, but that the neurohormone contributes to the regulation of the respiratory system by fine-tuning of breathing in order to restore homeostasis. We discuss evidence in support of this presumption. Specifically, vasopressinergic neurons innervate the brainstem nuclei involved in the control of respiration. Moreover, vasopressin V1a receptors (V1aRs) are expressed on neurons in the respiratory centres of the brainstem, in the circumventricular organs that a lack blood-brain barrier, and on the chemosensitive type I cells in the carotid bodies. Finally, peripheral and central administrations of AVP or antagonists of V1aRs increase/decrease phrenic nerve activity and pulmonary ventilation in a site-specific manner. Altogether, the findings discussed in this review strongly argue for the hypothesis that vasopressin affects ventilation both as a blood-borne neurohormone and as a neurotransmitter within the central nervous system.